PENGARUH FASILITAS DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA HOLIDAY HOTEL DI KOTA BATAM - Feni Maryati; Nur Elfi Husda (Magister Manajemen STIE Bank BPD Jateng, 2020)
This study aims to determine the effect of facilities and service quality on customer satisfaction at Holiday Hotels in Batam. Sampling was determined using purposive sampling and the total sample of 136 respondents based on Slovin formula. Data collection techniques in this study used a questionnaire. The collected data were analyzed using multiple linear regression analysis with the help of SPSS (Statistic Product and Service Solution) version 23. The results of this study indicate that from the results of the t test, it is known that the independent variables namely facilities significantly influence customer satisfaction, service quality significantly influences customer satisfaction, and facilities significantly influence service quality. From the results of the f test, the dependent variable is customer satisfaction, that facilities and service quality simultaneously and simultaneously have a significant effect on customer satisfaction at the Holiday Hotel in Batam.